S06-5 Towards an assessment of health risks associated with exposure to gamma radiation within a cohort of ontario uranium miners. (1st September 2016) - Do, Minh T; Navaranjan, Garthika; Berriault, Colin; Villeneuve, Paul; Demers, Paul
Abstract : Adverse health effects associated with exposure to gamma radiation have historically been ignored in assessing health risks among underground uranium miners. However, recent studies have shown evidence of excess mortality of heart diseases, leukaemia, and solid cancers associated with increased cumulative doses of external gamma radiation. As such, this study aims to quantify health risks associated with increasing cumulative doses of gamma radiation within a cohort of Ontario Uranium Miners (OUM). The OUM cohort was created using the Mining Master File, with data from annual screening exams, and the National Dose Registry for radiation exposure. The cohort included Ontario miners who worked for at least one week in uranium mines. Cancer diagnoses (1969–2005) and causes of death (1954–2007) were determined nationally in this cohort through probabilistic record linkage. Individual gamma measurements were obtained from 1981 onwards using dosimeters specifically designed for underground miners. Prior to 1981, a predictive model was used. Analyses were restricted to workers employed at the single largest mine in the region, where dose reconstruction has been completed. Poisson regression was used to estimate relative risks and their 95% confidence intervals with levels of cumulative gamma radiation exposure. Within this sub-cohort, there were 12, 953 miners employed between 1954–1992 contributing 431, 655 person-years of observation. No statistically significant excesses in mortality (10-year lag) were observed for lung cancer (RR = 1.11, 95% CI: 0.085–1.45) or cardiovascular diseases (5-year lag) (RR = 1.01, 95% CI: 0.87–1.22). Statistically significant increased risk was observed for all leukemias combined when comparing highest cumulative dose category (>14 mSv) to the referent (0 mSv) group (RR = 2.58, 95% CI: 1.06–6.3). While consistent with previous study, this finding was surprising given the low cumulative dose. Further research is necessary to understand the risks of hematologic cancers from low-dose exposures to gamma radiation. This work was funded by the Canadian Nuclear Safety Commission.